Effects of plant species diversity on nematode community composition and diversity in a long-term biodiversity experiment - Peter Dietrich; Simone Cesarz; Tao Liu; Christiane Roscher; Nico Eisenhauer (Oecologia, 2021)
Diversity loss has been shown to change the soil community; however, little is known about long-term consequences and underlying mechanisms. Here, we investigated how nematode communities are affected by plant species richness and whether this is driven by resource quantity or quality in 15-year-old plant communities of a long-term grassland biodiversity experiment. We extracted nematodes from 93 experimental plots differing in plant species richness, and measured above- and belowground plant biomass production and soil organic carbon concentrations ( C org ) as proxies for resource quantity, as well as C / N leaf ratio and specific root length (SRL) as proxies for resource quality. We found that nematode community composition and diversity significantly differed among plant species richness levels. This was mostly due to positive plant diversity effects on the abundance and genus richness of bacterial-feeding, omnivorous, and predatory nematodes, which benefited from higher shoot mass and soil C org in species-rich plant communities, suggesting control via resource quantity. In contrast, plant-feeding nematodes were negatively influenced by shoot mass, probably due to higher top–down control by predators, and were positively related to SRL and C / N leaf , indicating control via resource quality. The decrease of the grazing pressure ratio (plant feeders per root mass) with plant species richness indicated a higher accumulation of plant-feeding nematodes in species-poor plant communities. Our results, therefore, support the hypothesis that soil-borne pathogens accumulate in low-diversity communities over time, while soil mutualists (bacterial-feeding, omnivorous, predatory nematodes) increase in abundance and richness in high-diversity plant communities, which may contribute to the widely-observed positive plant diversity–productivity relationship.